First report on adulticide susceptibility status of aedes albopictus, culex quinquefasciatus, and culex vishnui from a pig farm in Tanjung Sepat, Selangor, Malaysia - Chen, C.D.; Low, V.; Lau, K.W.; Lee, H.L.; Nazni, W.A.; Heo, C.C.; Azidah, A.A.; Sofian-Azirun, Mohd (2013)
The present study aims to investigate the susceptibility status of Aedes albopictus, Culex quinquefasciatus, and Cx. vishnui collected from a pig farm in Tanjung Sepat, Selangor, toward 11 insecticides representing the classes of organochlorines, carbamates, organophosphates, and pyrethroids. The results of a World Health Organization adult mosquito bioassay revealed that Ae. albopictus, Cx. quinquefasciatus, and Cx. vishnui exhibited different susceptibility toward various insecticides. Overall, pyrethroids were able to induce rapid knockdown for all test mosquito species. The pyrethroids lambdacyhalothrin and etofenprox were able to cause high mortality (>80) of all 3 species. The findings of the present study will benefit local authorities in selecting appropriate dosage of insecticides to be used in mosquito control in this area.